Pengaruh IkhtilÃ¢f al-HadÃ®th terhadap Penalaran Hukum Islam - Masruhan, Masruhan (ISLAMICA: Jurnal Studi Keislaman, 2013)
Difference of opinion is highly respected in Islam. The Prophet of Islam is even reported to have said that, âdifference of opinion is divine providenceâ. This paper tackles this issue particularly within the science of prophetic tradition, and relates it to the way Muslim legalists develop the logics of law. The paper first argues that difference of opinion is not only natural but also needed in legal and social life. It is alsoâviewed in terms of social conflictâa requirement for a social integration. The paper speaks of the two sources of Islamâthe QurâÃ¢n and the prophetic traditionâas supportive of this difference of opinion and shows that the prophet, his companions, and closest followers are all involved in debate stemmed from their difference of opinion. This difference is the natural consequence of the difference in the level of understanding, different language, culture, way of thinking, custom, and the extent to which the companions are in engaged in the activities of the prophet.